Investigating the Factors Affecting the Teaching Efficacy of Filipino Science Teachers: A Correlational Study - Panergayo, Albert Andry Echor; Gregana, Clarissa Fajardo; Panoy, Julie Fe Dimaunahan (Jurnal Pendidikan Progresif, 2022)
This study investigated the factors influencing the science teaching efficacy of Filipino science teachers. A correlational research design was employed to collect the data from 261 Filipino science teachers using adapted and validated research instrument, encoded and administered via web-based program. The results uncovered that student technology use, 21st century learning attitudes, and teacher leadership attitudes are not significant predictors of science teaching efficacy.  The teaching outcome expectancy beliefs, STEM instruction, and STEM career awareness, however, can significantly explain the variation in the science teaching efficacy of the respondents. This indicates that teacher actions in science classroom, their pedagogical practices, and their awareness to STEM-fields should be considered in crafting capacity building program for science teachers. These factors are crucial in enhancing of teacher quality of science educators, thereby, uplifting the quality of science education in the country. Keywords: science teaching efficacy, stem career awareness, stem instruction, teaching outcome expectancy beliefs.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202203